THE LEGITIMIZATION OF POSTCOMMUNIST REGIMES - Шаповаленко, М. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
Was investigated features of legitimize communist regimes. On the basis of the practice of institutional changes in the measurement of the constitution concluded that the instability of the legal framework and arrogant attitude to the rules of the political actors regimes condemns ongoing process delegitimize. Furthermore, foundations eroded the value of post-communist transformation. Emphasized that to overcome the syndrome of permanent delegitimize should rely more on formal institutions and rules. Emphasized that to overcome the syndrome of permanent delegitimize should rely more on formal institutions and rules.